High dose and long-term use of spironolactone induce gynecomastia in an elderly man with chronic heart failure: a case report - Putu Giani Anabella Bestari Putri; Nurfitriani Nurfitriani; I Gusti Ayu Suryawati (DiscoverSys Inc., 2021)
Introduction: Gynecomastia is caused by an imbalance of estrogen and androgen in the male breast tissue. It can be divided into three causes, physiological, drug-induced, and idiopathic. Spironolactone is a potassium-sparing diuretic that has known to pose an antiandrogen effect and can cause gynecomastia.Case Description: A 75 years old man came for a regular cardiac examination at the hospital. He complained of tenderness and pain at his right breast for the last six months and only getting worse since the previous two weeks. He had a regular appointment with a cardiologist after diagnosed with Chronic Heart Failure Functional Class III, Suspected as Coronary Artery Disease, Hypertensive Heart Disease since January 2017. The patient regularly takes Furosemide 40 mg once a day, Clopidogrel 75 mg once a day, Valsartan 10 mg once a day, Bisoprolol 1.25 mg once a day, and Spironolactone 100 mg once a day. On physical examination, tenderness was felt on the right breast. Fine-needle aspiration cytology examination of the right breast was conducted, the finding was compatible with gynecomastia.Conclusion: Gynecomastia is a breast enlargement in men that occurred due to hormonal imbalance and most often caused by the side effect of a high-dose and long-term use of Spironolactone. Discontinuation of the spironolactone treatment or switching to other therapy is recommended. However, gynecomastia should not be used as a reason for not prescribing Spironolactone to patients with severe heart failure.